Amino Acid-Dependent Alterations in Cell Wall and Cell Morphology of Deinococcus indicus DR1 - Chauhan, Deepika; Srivastava, Pulkit Anupam; Ritzl, Barbara; Yennamalli, Ragothaman M.; Cava, Felipe; Priyadarshini, Richa (Frontiers in Microbiology, 2019)
Deinococcus radiodurans exhibits growth medium dependent morphological variation in cell shape, but there is no evidence whether this phenomenon is observed in other members of the Deinococcaceae family. In this study we isolated a red-pigmented, aerobic, Deinococcus indicus strain DR1 from Dadri wetland, India. This D. indicus strain exhibited cell-morphology transition from rod- shaped cells to multi-cell chains in a growth- medium dependent fashion. In response to addition of 1% casamino acids in the minimal growth medium, rod-shaped cells formed multi-cell chains. Addition of all 20 amino acids to the minimal medium was able to recapitulate the phenotype. Specifically, a combination of L-methionine, L-lysine, L-aspartate and L-threonine caused morphological alterations. The transition from rod shape to multi-cell chains is due to delay in daughter cell separation after cell division. Minimal medium supplemented with L-ornithine alone was able to cause cell morphology changes. Furthermore, a comparative UPLC analysis of PG fragments isolated from D. indicus cells propagated in different growth media revealed alterations in the PG composition. An increase in the overall cross-linkage of PG was observed in muropeptides from nutrient rich TSB and NB media versus PYE medium. Overall our study highlights that environmental conditions influence PG composition and cell morphology in D. indicus